Government development expenditure and government debt in Malaysia - See, Yong Liang (Universiti Malaysia Sarawak (UNIMAS), 2015)
Government debt in Malaysia sharply increased in recently years and Malaysian government run budget deficit along the years since 1997 Asian financial crisis. Government debt accumulated mainly due to overspending of its finance. This study is done to determine the relationship between government development expenditure components and government debt in Malaysia for the period of 1970-2014. The variables adopted in the analysis are government debt (GD), development expenditure for defense and security (DEFS), for economic services (ECOS) and for social services (SOCS). All the variables has been transform into natural logarithm form for analysis purpose. The methods used in this study are Augmented Dickey-Fuller (ADF) Unit Root Test, Phillips-Perron (PP) Unit Root Test, Johansen-Juselius Cointegration test and Vector Error Correction Model (VECM)-based Granger Causality test. The findings of this study confirm that LGD, LDEFS, LECOS and LSOCS are cointegrated in the long run. LECOS and LSOCS have a significant and positive relationship with LGD; while LDEFS has negatively impact on LGD.